PENERAPAN METODE STORY READINGMELALUI MODEL PEMBELAJARAN PICTURE AND PICTUREUNTUK MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIA 5 - 6 TAHUN DI TK MUSTIKA BUNDA PEKANBARU - Armaita, Armaita (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This study aims to improve speaking skills of children ages 5-6 through story reading method through learning model picture in TK Mustika Bunda Pekanbaru. The method used was classroom action research. A class act that researchers do is use the method of reading the story through picture picture learning model to improve speaking skills of children aged 5-6 years in TK Mustika Bunda Pekanbaru, and observed by the observer. The sample taken is a TK Mustika Bunda Pekanbaru with the number of children of 20 people, consisting of 13 men and 7 women. Data collection techniques in this research is through observation of teachers and children and talk capability data of children aged 5-6 years with the use of methods of story reading through learning model picture picture. The results obtained by using the method of story reading can improve speaking skills of children aged 5-6 years in TK Mustika Bunda Pekanbaru. The percentage increase in the ability to speak the child at the age of 5-6 years using the Story Reading by drawing the series in TK Mustika Bunda Pekanbaru from the first cycle to the second cycle was 20.5%. The implication of this study is the use of methods of story reading through picture picture learning model used properly, can improve speaking skills of children aged 5-6 years in TK Mustika Bunda Pekanbaru.